Possible mechanism of structural transformations induced by StAsp-PSI in lipid membranes - Muñoz, F.F. (2014)
In the present work we have analyzed the effect of StAsp-PSI (plant-specific insert of potato aspartic protease) on the structural and thermotropic properties of the major phospholipid types of bacterial and animal cells. Results obtained suggest that StAsp-PSI induces a destabilization of the membrane bilayers, depending on the time of interaction between the protein and the bilayers, rather than on its concentration. This temporal delay would be consistent with a lateral diffusion of StAsp-PSI monomers to assemble into aggregates to form pores. Like with the results previously reported for the StAsp-PSI circular dichroism, data obtained here from IR spectroscopy show that there are slight changes in the StAsp-PSI secondary structure in the presence of lipid membranes; suggesting that these changes could be related with the StAsp-PSI self-association. Results obtained from steady-state fluorescence anisotropy and differential scanning calorimetry assays suggest that StAsp-PSI interacts with both uncharged and negatively charged phospholipids, modulates the phase polymorphic behavior of model membranes and partitions and buries differentially in the membrane depending on the presence of negatively charged phospholipids.